Microbial characterization of belacan(fermented shrimp paste) and its potential as a plant-growth promoting agent of oyster mushroom (Pleurotus ostreatus) - Abedelazeez, Khudair J.D.; Zaini, Nurul Solehah Mohd; Fauzi, Nur Aisyah Syahirah Ahmad; Zainuddin, Nurazlin; Tiun, Xin Ci; Kesvaran, Hosynaa Elang; Yaacob, Jamilah Syafawati; Rahim, Muhamad Hafiz Abd (Hibiscus Publisher Enterprise, 2024)
Belacan, or fermented shrimp paste, is produced through the fermentation of small shrimps and salts under specific conditions. As a result of spontaneous fermentation, belacan harbors a diverse microbial community comprising bacteria, fungi, and yeast. These microorganisms possess the potential to influence not only human health but also plant health. Hence, this project seeks to elucidate the bacterial characteristics of belacan in promoting the growth and development of oyster mushrooms (Pleurotus ostreatus). Through the identification and isolation of two prominent bacterial strains, Lysinibacillus fusiformis and Bacillus velezensis, it has been revealed that these bacteria can benefit plant growth. Further investigation has demonstrated that these bacteria serve as plant growth-promoting bacteria (PGPB), exhibiting positive effects on phosphate solubilization, indole-3-acetic acid (IAA) levels, antifungal activity, and the physical characteristics of oyster mushrooms.